Kematangan Etika Pada Pendidikan Akuntansi : Tinjauan After Virtue - Mujtaba, Muhammad Irsyad Elfin; Prestiani, Tri Sangga (Politeknik Ganesha Medan, 2024)
The accounting scandals that have occurred so far are thought to be the result of ethical failures and the role of accounting education has been asked to be responsible for them. However, the ethical maturity of accounting students during their educational process is still questionable. The influence of mainstream Anglo-American capitalist culture is the cause. To address this, Alasdair MacIntyre's After Virtue moral discourse is proposed with the main focus being to answer the question